Spatio-temporal earthquake clustering in the Western Corinth Gulf - Karagianni, E.; Paradisopoulou, P.; Karakostas, V. (Bulletin of the Geological Society of Greece, 2013)
Corinth Gulf has been studied, thoroughly using multidisciplinary approaches (geological, seismological, geodetic etc), which revealed its complicated tectonic behaviour. In the last five years or more, an intense continuous microseismic activity is observed in the westernmost part of the gulf covering the area from west of Aigio to the area west of Rio Antirrio strait, near the city of Patras. Aiming to study in detail the properties of this microseismic manifestation, the recordings of the Hellenic Unified Seismological Network (HUSN) are used to accurately determine the focal coordinates of earthquakes with magnitudes M=1.5 or more. Relocation was performed using the HYPOINVERSE program, for all available data for the period 2010-2011 when earthquakes up to magnitude M=5.5 occurred. The space time plot of the epicentres shows that seismicity is not random in the area but formed distinctive clusters, indicating an E-W striking seismic zone whose patches are successively activated for certain periods. The present work deals with the investigation of spatio-temporal evolution of seismicity with the intention to examine the migration of seismicity and multi-segment activation.